Implementación de un sistema de contabilidad para la empresa Agrícola Marinita Cía. Ltda. del recinto las Palmas, Cantón La Maná, en el período 2011 - Goya Anzules, Jenny Johanna (2013)
The present research hadaimed to implement an accounting system at Marinita Cía. Ltd. Agricultural Enterprise, which is considered important in the banana production sector, as an organization which has in its mission and vision of continuous improvement plans, seeking to achieve in a short time to become one of the best companies and to offer a quality product to both national and international markets.The main objective of this research was implementing an accounting system that allows to get economic and financial information for making good decisions and to contribute to the progress of it. The researchers must indicate that it has emerged as one of the alternatives to improve the management of agricultural business information, applyingan exploratory research that allowed to describe the phenomenon under research, and also facilitated know the characteristics of the study problem, identify the procedures carried out by the responsible people of various management activities and performance of the company, and finally helped the company to identify the causes of the problems in its accounting system, so the researchers could identify the independent variable (the implementation of accounting system) and the dependent variable (agricultural accounting), in order to deliver a proposal to solve the problem mention before.The research has been concluded that the Agricultural Enterprise Cía. Ltd., improved its management related with financial information by providing an essential management tool for making correct decision and to face to the competition in better conditions and national and international stakeholders.